Impact of COVID-19 on pornography use: Evidence from big data analyses. - Way Kwok-Wai Lau; Lionel Ho-Man Ngan; Randolph Chun-Ho Chan; William Ka-Kei Wu; Benson Wui-Man Lau (PLoS ONE)
Introduction Coronavirus disease 2019 (COVID-19) has led to radical changes in social distancing awareness and affected social relationships. Owing to large-scale lockdown, home quarantine and social distancing requirements, it was anticipated that sexual activities would be severely impacted. However, retrospective self-report studies showed that pornography use and autoerotism increased during the pandemic. Aim This study used big-data databases available on the Internet to investigate factors that modulated pornography use during the pandemic. Methods Daily relative search volume (RSV) data from Google Trends for the period from 24 February 2020 to 13 July 2020 were extracted. Pornhub traffic data were extracted from the Pornhub Insights website, for the period from 24 February 2020 to 13 July 2020. The parameter was defined as 'percent change in traffic compared to an average day in 2019'. The number of daily new cases of COVID-19 was extracted from the database on Our World in Data. Outcome measures The normality of the data was examined using the Shapiro-Wilk test. All variables included in this study were non-normally distributed. Therefore, non-parametric tests or parametric tests with bootstrapping were adopted where appropriate. Results According to Google Trends, the RSV for 'pornography' increased after late March 2020, which is close to the date when the World Health Organization declared COVID-19 a global pandemic. The number of daily new cases of COVID-19 was positively correlated with the traffic of Pornhub, a popular pornography website, and the RSV for 'pornography'. Moderation analysis demonstrated a significant main effect of daily new cases of COVID-19 and the RSV for 'social distancing' in predicting Pornhub traffic/RSV for 'pornography'. Furthermore, the RSV for 'social distancing' significantly moderated the relationship between daily new cases and Pornhub traffic/RSV for 'pornography'. A stronger COVID-pornography use association was observed with increased social distancing awareness. Conclusion Increased pornography consumption during the pandemic was observed, and it was associated with the severity of the pandemic. Social distancing awareness could be a key factor influencing interest in and use of pornography. Further studies on the changes in sexual desire and birth-rate control are worthwhile because long-term public health may be affected by the changes in sexual behaviour during the pandemic.